Determination of Antioxidant Properties of Ethanol and Water Extracts of Achillea millefolium L. (Yarrow) - Keser, Serhat; Celk, Sait; Turkoglu, Semra; Yilmaz, Okkes; Turkoglu, Ismail (Asian Journal of Chemistry, 2011)
Achillea millefolim L. is a member of the Asteraceae family that is commonly referred to as 'yarrow' and has been used in folk medicine against several disturbances including skin inflammations, spasmodic and gastrointestinal disorders, as well as hepato-biliary complaints. Ethanol and water extracts were prepared from powdered A. millefoliun flowers, leaves and seeds. In this study, antioxidant properties were studied by 2,2-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS(center dot+)) radical scavenging, 1,1-diphenyl-2-picryl-hydrazyl free radical (DPPH(center dot)) scavenging, superoxide anion (O(2)(center dot-)) radical scavenging, reducing activity and ferrous metal chelating activity assays. In conclusion, A. millefolium flowers, leaves and seeds had effective ABTS(center dot+) and DPPH(center dot) radical scavenging, superoxide anion radical scavenging, reducing power and metal chelating activities. Additionally, these various antioxidant activities were compared with BHA, BHT and alpha-tocopherol as reference antioxidants.
Keywords: Achillea millefolium; Yarrow; Antioxidant capacity; DPPH(center dot); ABTS(center dot+); Superoxide radical